Rancang Bangun Gelang Locator Pasien Terkonfirmasi Covid-19 dengan Metode Haversine sebagai Pengidentifikasian Pelanggaran Zona Aman Isolasi Mandiri Menggunakan Komunikasi Lora (Long Range) - Maulana, Ahmad Afan; Alfita, Riza; Ibadillah, Achmad Fiqhi (Universitas Semarang, 2021)
Positive cases of COVID-19 continue to grow rapidly. This prompted the government to make new rules in the form of various types of health protocols. One of them is the implementation of the self-isolation protocol for confirmed COVID-19 patients. Self-isolation is a rule that requires confirmed patients to stay at home until the specified time limit to break the chain of COVID-19 development. However, it is suggested and as a rule that there are still many ODP and PDP who still violate the rules of self-isolation from the government. The ODP and PDP still roam freely without thinking about the impacts and risks to their surroundings. With the departure of confirmed patients, the risk of developing COVID-19 becomes greater. In this study, a confirmed patient locator bracelet was made that can map the position of the patient based on latitude and longitude. The latitude and longitude data from the bracelet is sent to the gateway by LoRa communication. LoRa communication is also used to minimize the dimensions of the bracelet. In addition to mapping the location of the patients, by applying the Heversine method this system is able to identify when a safe zone violation occurs in the form of a change in the color of the marker. In the future, it is hoped that this system will be able to handle the problem of developing COVID-19 caused by confirmed patients who still violate the self-isolation protocol.